SHERLOCK HOLMES, A MANGLE AND A MEANINGLESS RITUAL: THE DEMONIC (OF) REPETITIONS IN POPULAR CULTURE - Brzostek, Dariusz (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The article focuses on the mechanism of repeating a formula in texts of popular culture and its relations to evoking the experience of the uncanny (uncheimlich) in the process of reception of popular narratives, both those alluding to the aesthetics of horror and those following other conventions (crime fiction, comedies, etc.). The essence of this experience is the audience’s discovery of (un-)expected repetitions of the same in something seemingly different, that is, an identical formula in a new, yet unknown, text. The methodological context for this analysis consists of J.G. Cawelti’s concept of formula, Freud’s theory of “the uncanny”, Harold Bloom’s concept of the anxiety of influence, and Frits Staal’s notion of “the meaningless ritual”. The texts analyzed herein are short stories by Stephen King, Arthur Conan Doyle, and Clive Barker as well as TV series Friends and Big Bang Theory.